Morphometric study of nutrient foramen of tibia in Jharkhand population - Kushwaha, Rajesh K.; Ranjan, Rajiv; Prasad, Makardhawaj (International Journal of Research in Medical Sciences, 2021)
Background: Nutrient foramen gives passage to the nutrient vessels which supply major portion of the bone even bone marrow. Many vascular foramina are present in all bones for the passage of blood vessels. In long bones many small vascular foramina are present at the ends through which epiphyseal and metaphyseal blood vessels passes. In the shaft of long bones one or two larger foramina are present through which nutrient vessels passes. Nutrient artery provides 70% to 80% blood supply of long bones in children and if blood supply is decreased, it may lead to ischemia of bone resulting into less vascularisation of metaphysis and growth plate. Thus precise topographical knowledge of nutrient foramen is necessary for the surgeons to save the nutrient vessels during surgical procedures i.e. fracture fixation, bone grafting etc. Damage to the nutrient artery causes avascular necrosis of bone. Methods: Total 70 dry bones of tibia were taken in the study, without knowledge of sex of the bone. Position, number and direction of the nutrient foramen were noted. Results: single nutrient foramina present in 91.43% of cases and double in 6% of cases. 97.14 % nutrient foramina are directed downward and 2.86% directed upward. 90% nutrient foramina present on posterior surface, 1.42% on lateral surface and 8.57% on lateral border. 75% of nutrient foramina present in upper 1/3 and 25% in middle 1/3. Primary nutrient foramina (>24 G) present in 89.47% and secondary nutrient foramina (<24 G) present in 10.53% of cases. Conclusions: A sound knowledge of nutrient foramen topography, prevent the injuries of vasculature of bone during surgeries.